SPE Annual Technical Conference and Exhibition 2008
DOI: 10.2118/115744-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reservoir Uncertainty on Selection of Advanced Completion Type

Abstract: Well performance prediction is a key Petroleum Engineering task. However, large discrepancies between Petroleum Engineering models and reality still frequently occur; despite the continuous increase in the complexity and predictive quality of reservoir models. To-day's field development decisions are still made with a high level of uncertainty in the underlying data and its economic impact. The degree of data uncertainty is greatest during the exploration stage, but decreases as the reservoir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…It has previously been shown by (Birchenko, Demyanov et al 2008;Grebenkin and Davies 2010) to be a suitable candidate for IW. It has previously been shown by (Birchenko, Demyanov et al 2008;Grebenkin and Davies 2010) to be a suitable candidate for IW.…”
Section: Iw Monitoring System Design Examplementioning
confidence: 99%
“…It has previously been shown by (Birchenko, Demyanov et al 2008;Grebenkin and Davies 2010) to be a suitable candidate for IW. It has previously been shown by (Birchenko, Demyanov et al 2008;Grebenkin and Davies 2010) to be a suitable candidate for IW.…”
Section: Iw Monitoring System Design Examplementioning
confidence: 99%
“…Birchenko et al examined the impact of ICDs and ICVs on the geological uncertainty. They showed ICVs were capable to reduce the production uncertainty up to 50% (Birchenko et al, 2008). Grebenkin showed that the impact of variations in parameters such as (barrier) shale and fault transmissibilities, inflated GOC or WOC can be mitigated by ICVs installation (Grebenkin, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…КИК позволяют гибко управлять скважиной на стадии разработки, уменьшая риск, вызванный изначальной неопределенностью различных параметров пласта. В предыдущей работе было показано, что интеллектуальная скважина способна уменьшить влияние неопределенности геологических параметров на прогноз добычи [1]. Существует два основных вида оптимизационных стратегий контроля скважин: «проактивная» и «реактивная» [4].…”
unclassified